Post-discharge decolonization of patients harboring methicillin-resistant Staphylococcus aureus (MRSA) USA300 strains: secondary analysis of the CLEAR Trial. (16th February 2023) - Gussin, Gabrielle M.; Heim, Lauren; Tjoa, Thomas; McKinnell, James A.; Miller, Loren G.; Gillen, Daniel L.; Sater, Mohamad R.A.; Grad, Yonatan H.; Singh, Raveena D.; Huang, Susan S.
Abstract: The CLEAR Trial recently found that decolonization reduced infections and hospitalizations in MRSA carriers in the year following hospital discharge. In this secondary analysis, we explored whether decolonization had a similar benefit in the subgroup of trial participants who harbored USA300, using two different definitions for the USA300 strain-type.